Analisis Laporan Keuangan untuk Menilai Tingkat Kesehatan Keuangan PT Cita Mineral Investindo, Tbk. - TJANDRA, RONOWATI; TRI AMANDA, MUTIA (ITB AAS INDONESIA, 2025)
The purpose of this study is to assess and determine the level of financial health of PT Cita Mineral Investindo, Tbk. during the period 2016 to 2020. This study uses quantitative data, obtained from the Indonesia Stock Exchange. The subject used by the author in this study is PT Cita Mineral Investindo, Tbk. While the object used is the financial report of PT Cita Mineral Investindo, Tbk. for 2016-2020. The analysis method used is the observation and documentation method. The method and technique of financial report analysis are based on data presented to assess the level of financial health based on Decree of the Minister of SOEs Number: KEP/100/2002. In the Decree of the Minister of SOEs, there are eight indicators that will be assessed, namely, ROE, ROI, Cash Ratio, Current Ratio, Collection Periods, Inventory Turnover, TATO, and Total Equity to Total Assets. The results of the study on the level of financial health of PT Cita Mineral Investindo, Tbk. obtained a predicate of unhealthy in 2016 with the BBB category and in 2017 with the BB category. For 2018 to 2020 the company received a healthy predicate. Changes in the total ratio score greatly affect the company's health level, so that during 2016-2020 the company obtained different health levels. PT Cita Mineral Investindo, Tbk. is expected to be able to improve its financial health level in order to obtain a healthy predicate with the AAA category by improving its financial performance.